Trapping and escape of viscous fingers in a soft Hele-Shaw cell - Peng, GG; Cuttle, C; Box, F; Guan, JH; Juel, A; Macminn, C; Pihler-Puzović, D (American Physical Society, 2022)
Viscous flow in the narrow gap between a rigid plate and a confined elastic solid has been observed to ‘choke’ at high flow rates, due to the deforming solid making contact with the plate and sealing the gap. When the viscous flow is driven by injection of a gas bubble, the advancing meniscus is susceptible to the viscous-fingering instability. By comparing fingering experiments with axisymmetric numerical simulations, we demonstrate that, depending on the width of the fingers, the fingering instability can either promote or suppress choking, i.e. cause the system to choke when an axisymmetric system would not, or vice versa.